An Empirical Analysis Of Meat Demand System Models In Peninsular Malaysia - Ahmed, Abdullahi Farah (2006)
The trend of meat consumption in Malaysia has shown a significant growth since early 1970’s. Total amount of meat per capita consumed has grown 57.3% from 1990 to 2003. Poultry and pork have been the dominant meats consumed in Peninsular Malaysia. However, the highest growths were chicken and beef, which have increased 99.15% and 57% from 1990 to 2003 respectively, while the consumption of pork per capita declined 22.3 %. Among the factors cited for this meat consumption growth were the consequences of economic development and associated changes in dietary patterns, taste and preferences in the country. Other reports indicated that the greater part of these changes had been due to consumer income growth and price effects besides high population growth. These spectacular changes make the answers to meat demand estimates in Malaysia more complex. Thus, empirical analysis employing the systems approach is used in this study.